Just do the rules of PEMDAS.

4-(x)/(x-2)=(-2)/(x-2)

Get rid of what's in common first, by multiplying both sides by (x-2). You're left with:

4-(x)=(-2)

4-(x)-4=(-2)-4

-x=-6

x=6

Get rid of what's in common first, by multiplying both sides by (x-2). You're left with:

4-(x)=(-2)

4-(x)-4=(-2)-4

-x=-6

x=6

4(x -2)- x/x-2(x-2) = -2/x-2(x-2)

4x -8-x = -2

4x-x = 6

3x = 6

x = 2

4x -8-x = -2

4x-x = 6

3x = 6

x = 2

The equation is in a fractional format or ratio and proportion; in which case, just do cross-multiplication...